Integration of Neuronal Excitatory and Inhibitory Functions in a Neuron Circuit Using Positive Feedback Field Effect Transistor - Park, Minseon; Kwon, Min-Woo (Journal of semiconductor technology and science, 2025)
Biological neurons play a crucial role in preventing excessive activation of the human brain and enabling efficient information processing by balancing excitatory and inhibitory functions. Neuromorphic chips and hardware based Spiking neural networks (SNNs) aim to replicate these biological neural systems in hardware. For instance, in artificial neural networks, biological neurons are represented by neuron circuits. Conventional analog neuron circuits utilize CMOS technology. However, existing CMOS-based analog neuron circuits show significant issues related to power consumption and area. Additionally, they fail to effectively integrate both excitatory and inhibitory functions. Therefore, in this study, we propose a neuron circuit that integrates both Neuronal excitatory and inhibitory functions using feedback field-effect transistor (FBFET). We fabricated the FBFET using TCAD Athena Simulation and designed the neuron circuit using SPICE mixed-mode simulations. By utilizing the threshold voltage adjustment characteristics of the FBFET’s control gate, we successfully inhibited neuron firing. Ultimately, we succeeded in integrating both excitatory and inhibitory signals using a single FBFET device. This work represents a significant advancement toward realizing bio-inspired neuromorphic computing systems. KCI Citation Count: 0